PERANCANGAN FILM ANIMASI PENDEK 2D SEBAGAI MEDIA KAMPANYE PENANGANAN ANXIETY DISORDER - Gede Pasek Putra Adnyana Yasa; Kadek Ayu Satyasusmaya Narpaduhita; Dewa Gede Purwita (Jurnal Bahasa Rupa, 2019)
More that 2 million cases of anxiety disorder occur in Indonesia every year. The term of anxiety disorder is not common in the community due to lack of campaigne and sosialisation. It will cause severe depresion and even commit suicide if it is not treated properly. The purpose of this design is to campaigne anxiety disorder’s sympton into the community through some one point of view who experinced anxiety disorder before and providing solution to the patients through two dimention animation media. This design using the theory of principle of animation, cinematography theory, design theory, aesthetic theory, semiotic theory and campaigne theory with qualitatif research methods and produces animation media that supported by social media, poster, x-banner, booklet, tote bag, t-shirt, pin and journal book using a hand drawing & vector tehnique in custom digital art and infographic style. Media is mad in accordance with the concept calm and educative. Calm concept applied through medium colour which is a blend colour of green and blue known as the colour of anxiety disorder awareness ribbon.